The connection between heart rate variability (HRV), neurological health, and cognition: A literature review - Arakaki, Xianghong; Arechavala, Rebecca J.; Choy, Elizabeth H.; Bautista, Jayveeritz; Bliss, Bishop; Molloy, Cathleen; Wu, Daw-An; Shimojo, Shinsuke; Jiang, Yang; Kleinman, Michael T.; Kloner, Robert A. (Frontiers in Neuroscience, 2023)
The heart and brain have bi-directional influences on each other, including autonomic regulation and hemodynamic connections. Heart rate variability (HRV) measures variation in beat-to-beat intervals. New findings about disorganized sinus rhythm (erratic rhythm, quantified as heart rate fragmentation, HRF) are discussed and suggest overestimation of autonomic activities in HRV changes, especially during aging or cardiovascular events. When excluding HRF, HRV is regulated via the central autonomic network (CAN). HRV acts as a proxy of autonomic activity and is associated with executive functions, decision-making, and emotional regulation in our health and wellbeing. Abnormal changes of HRV (e.g., decreased vagal functioning) are observed in various neurological conditions including mild cognitive impairments, dementia, mild traumatic brain injury, migraine, COVID-19, stroke, epilepsy, and psychological conditions (e.g., anxiety, stress, and schizophrenia). Efforts are needed to improve the dynamic and intriguing heart-brain interactions and overall health.